ANALISIS BEBAN KERJA UNTUK MENENTUKAN KEBUTUHAN TENAGA KERJA MENGGUNAKAN METODE FULL TIME EQUIVALENT (FTE) PADA PT SO GOOD FOOD - Akbar Gunawan; Kee Evelyne; Ade Irman Mutakin; Hadi Setiawan; Dhena ria Barleany; Maria Ulfah (Prodi Teknik Industri, Fakultas Teknik, 2023)
Qualified human resources are the most important factor in an organization or company. Human resources are one of the factors that can be a source of excellence for an organization or company to achieve efficiency, effectiveness and productivity in carrying out its business. The role of human resources is very important at PT So Good Food. Efficiency in the field of human resources is related to the workload that must be borne by an organizational unit. Planning and managing human resources can be done by making an appropriate analysis of the activities that occur and the resulting workload or by optimizing the number of employees so that they carry out their work activities properly. One of the workload calculation methods is the Full Time Equivalent (FTE) method. This study aims to determine the workload received by each employee and determine the optimal number of workers at PT So Good Food using the Full Time Equivalent (FTE) method. Based on the results of calculations that have been carried out using the FTE method, purchasing and logistics managers obtained an FTE index of 1.25, which means less than 1.28, the workload is normal or fit, while the purchasing staff has a workforce of 3 people so that the total owned FTE index of 3.75 which is rounded to 4, in the finance and accounting staff which totaled 3 people, a total FTE index of 3.75 was obtained which was rounded to 4, and the account receivable staff had a total workforce of 3 people so that the total index Owned FTE is 3.75 which is rounded to 4, so the workload is overloaded so that an additional 1 worker is needed